VIDEO GASTROSCOPIC CHARACTERISTICS OF ASYMPTOMATIC GASTRIC DISEASES IN PATIENTS WITH OBESITY AND TYPE 2 DIABETES MELLITUS - Khakimov, M.Sh.; Sattarov, O.T.; Khakimov, I.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. Our study aimed to study the morphofunctional state of the stomach, considering the quantitative density of endocrine cells producing somatostatin and gastrin in patients with obesity and type 2 diabetes mellitus, and to assess the effectiveness of anti-Helicobacter pylori therapy. Material. Patients with obesity and type 2 diabetes mellitus in combination with asymptomatic gastric pathology. Results. Stomach diseases in patients with obesity and type 2 diabetes mellitus have their clinical characteristics and the course of the pathological process. Exacerbation of gastric ulcer and chronic gastritis is often asymptomatic or with minimal clinical manifestations, and in almost 1/3 of cases, an ulcerative defect in the stomach is a diagnostic finding. The clinical picture of gastric pathology depends on the duration and severity of type 2 diabetes mellitus. Conclusion. The high incidence and degree of H.pylori infection in patients with gastric pathology combined with obesity and type 2 diabetes mellitus depend on the duration and severity of diabetes. The failure of first-line eradication therapy is associated with antibiotic resistance.